2012
DOI: 10.1111/j.1741-4520.2012.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel CRLF1 gene mutation in a newborn infant diagnosed with Crisponi syndrome

Abstract: Crisponi syndrome is an infrequently described disorder with autosomal recessive trait. It is characterized by extensive muscular contractions in the face after even minimal stimuli or crying, hypertonia, opisthotonus, camptodactyly, and typical facial features. Muscle contractions attenuate during rest or when the infant calms down. As a recently described new disease, Crisponi syndrome may be confused with epileptic manifestations. Most of the patients die in the first months of life due to hyperthermia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Seventeen cases evaluated in this study had been included in previous publications. 3,[12][13][14][15][16][17][18][19][20][21][22] Statistics Statistical analyses were performed using Statistica 9.1 (StatSoft, Tulsa, OK) and SAS 9.2 (Cary, NC). The frequencies were compared using w 2 tests with adequate corrections and the Fisher exact probability test with Freeman-Halton extension for 2Â3 and 2Â4 tables when applicable.…”
Section: Materials and Methods Study Populationmentioning
confidence: 99%
“…Seventeen cases evaluated in this study had been included in previous publications. 3,[12][13][14][15][16][17][18][19][20][21][22] Statistics Statistical analyses were performed using Statistica 9.1 (StatSoft, Tulsa, OK) and SAS 9.2 (Cary, NC). The frequencies were compared using w 2 tests with adequate corrections and the Fisher exact probability test with Freeman-Halton extension for 2Â3 and 2Â4 tables when applicable.…”
Section: Materials and Methods Study Populationmentioning
confidence: 99%
“…Mutations were further identified in several typical CS/ CISS1 patients [Cosar et al, 2011;Dessi et al, 2012;Hahn et al, 2010;Hakan et al, 2012;Herholz et al, 2011;Okur et al, 2008;Thomas et al, 2008;Uzunalic et al, 2013;Yamazaki et al, 2010]. Patients with CS/CISS1 are originating from several countries, mostly from Sardinia or Turkey, and recently a Japanese patient with a mutation in CRLF1 was reported [Yamazaki et al, 2010].…”
Section: Discussionmentioning
confidence: 95%
“…Growth delay, developmental delay, decrease pain sensation, and hyperintense lesions in the subcortical white matter on the brain MRI were reported with some of the patients, basic hematologic and biochemical workup usually does not show any abnormalities [5, 8, 14, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…It was found that both CISS and CS were caused by mutation in the same gene; the cytokine receptor-like factor 1 ( CRLF1) [3, 4]. Over the last 10 years it has been proven that CS and CISS represent a spectrum of one disorder with some differences in the clinical features between infancy and childhood rather than two entities [57]. …”
Section: Introductionmentioning
confidence: 99%